2020
DOI: 10.3389/fphar.2019.01555
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 and the Underlying Therapeutic Promise of Neurodegenerative Disorders

Abstract: Neurodegenerative disorders (NDDs) are a group of chronic progressive neurological diseases based on primary neurodegeneration. The common pathological characteristics of various NDDs are neuronal degeneration, deletion, glial cell proliferation, and hypertrophy at specific locations in the nervous system. Proliferation and hypertrophy of microglia are manifestations of inflammation. MicroRNAs (miRNAs) have emerged as pivotal regulators of glial cells. MiRNAs are small non-coding molecules that regulate gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 98 publications
(105 reference statements)
1
36
0
Order By: Relevance
“…Despite the critical role of miR-124 in neuronal differentiation and neurite outgrowth [ 30 ], its increased levels were associated with pathological events in neurodegenerative diseases, including ALS [ 24 , 31 ]. We have previously demonstrated that miR-124 is upregulated in NSC-34 mSOD1 MNs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the critical role of miR-124 in neuronal differentiation and neurite outgrowth [ 30 ], its increased levels were associated with pathological events in neurodegenerative diseases, including ALS [ 24 , 31 ]. We have previously demonstrated that miR-124 is upregulated in NSC-34 mSOD1 MNs [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its decrease was shown to attenuate NO production, while its upregulation was highlighted as increasing the risk of hypoxic injury and angiogenesis decrease, or even to be protective in SC injury [ 56 , 57 ]. In addition, miR-124 dysregulation was linked to the development of neurodegenerative disorders [ 31 ] and to several immune-system related pathways [ 58 ]. On the other hand, potential benefits of miR-124 upregulation were referred in Alzheimer’s disease through negative regulation of BACE1 expression [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR‐124 plays key regulatory roles in neurological disease, 20 and its expression is decreased in patients with epilepsy 21 ; however, Brennan et al reported that increased miR‐124 does not alter epileptogenesis during the chronic phase of a kainic acid–induced epileptic rat model 22 . Further mechanistic analyses expounded on the reasons why miR‐124 does not influence spontaneous recurrent seizures; miR‐124 not only prevents hippocampal neuron restrictive silencing factor (NRSF) upregulation but also promotes the activation of hippocampal microglia and inflammatory cytokines 22 .…”
Section: Mir‐124mentioning
confidence: 99%
“…They play an important role in cell fate determination, cell differentiation, organ development, and physiology and are also involved in various pathologies in humans (Almeida et al, 2011 ; Desvignes et al, 2015 ). miRNAs regulate target gene mRNA mainly by cutting off the target gene’s RNA molecule, thereby inhibiting target gene translation and inhibiting recombination (Han et al, 2019 ). By binding to the RNA-induced silencing complex, the nucleotide sequence of miRNA allows targeted base pairing with the 3′-untranslated region of complementary mRNA.…”
Section: Involvement Of Mirnas In Astrocyte Dysfunction In Neurodegenmentioning
confidence: 99%